PERAN GURU SEBAGAI MODEL DALAM PERKEMBANGAN NILAI AGAMA DAN MORAL PADA ANAK USIA DINI KELOMPOK B DI TK MARAQITTA’LIMAT TEMBENG PUTIK TAHUN AJARAN 2023/2024 - Irmayanti; Nurul Yakin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Early childhood education has a very important role in optimizing children's development potential. As a PAUD teacher, you have the responsibility to teach positive values ​​and morality to children. Apart from teaching religious and moral values, PAUD teachers must also be role models for children. This research aims to describe the role of teachers and the factors that influence the development of religious and moral values ​​in early childhood group B at Maraqitta'limat Tembeng Putik Kindergarten. This research used a descriptive qualitative approach and involved two teachers. Data was collected through observation, interviews and document analysis. Data analysis was carried out qualitatively with stages of data reduction, data presentation, and drawing conclusions. The results of the research show that the development of religious and moral values ​​in early childhood at the Maraqitta'limat Tembeng Putik Kindergarten is starting to show progress. This can be seen from the children's behavior, such as when praying they are able to follow the teacher, showing respect between students and the teacher, as well as the rules of conduct when lining up before entering class.